POTENSI FILTRAT Trichoderma asperellum TKD DALAM MENGHAMBAT KONTAMINASI Aspergillus parasiticus PADA BIJI KACANG TANAH - Rahmadanty, Nasha Hadi; Darmayasa, Ida Bagus Gede; Parwanayoni, Ni Made Susun (SIMBIOSIS, 2023)
iThis researchhaimed to determineethe potency off  Trichoderma asperellum  TKD ffiltrate in inhibiting Aspergillus parasiticus  contamination in peanut seeds. The treatment given to A. parasiticus  was done in vitro and in vivo. In vitro there were three types methods, dual culture  and the inhibition test of the  T.asperellum TKD ifiltrate using the diffusion well and the colony method with concentrations of 40% (v/v), 50%(v/v), 60%(v/v),70%(v/v) and 80%(v/v). While in vivo, it was done on peanut seeds added   T.asperellum i TKD filtrate with some concentrations similar to the treatment given in vitro. The parameters measured in vitro test were determined through PIRG (Percentage Inhibition of Radial Growth) and diameter inhibition zone, in vivo test parameter was the   A. parasiticus  colony populations. The results showed T.asperellum TKD filtrate significantly (P?0,05) was able to inhibit A. parasiticus growth iin vitro and iin vivo. The percentageeof T.asperellum  TKD bland power against A.parasiticus  in vitro with the highest dual culture method was 60.65%. In the method of colony and diffusion well, the concentration of 80% was the highest concentration in inhibiting A. parasiticus,  which were 83.00±1.60% and 15.09±0.12 mm.  T.asperellum  TKD filtrate with a concentration of 80% added to peanut seeds had the highest inhibition on the number of population of A. parasiticus  colonies with a percentage decrease   of 88.3%.